Microbial Community Structure and Function Indicate the Severity of Chromium Contamination of the Yellow River - Pei, Yaxin; Yu, Zhengsheng; Ji, Jing; Khan, Aman; Li, Xiangkai (Frontiers in Microbiology, 2018)
The Yellow River is the most important water resource in northern China. In the recent past, heavy metal contamination has become severe due to industrial processes and other anthropogenic activities. In this study, riparian soil samples with varying levels of chromium (Cr) pollution severity were collected along the Gansu industrial reach of the Yellow River, including samples from uncontaminated sites (XC, XGU), slightly contaminated sites (LJX, XGD), and heavily contaminated sites (CG, XG). The Cr concentrations of these samples varied from 83.83 mg•kg-1 (XGU) to 506.58 mg•kg-1 (XG). The chromate (Cr (VI)) reducing ability in the soils collected in this study followed the sequence of the heavily contaminated > slightly contaminated > the un-contaminated. Common Cr remediation genes chrA and yieF were detected in the XG and CG samples. qRT-PCR results showed that the expression of chrA was up-regulated 4-fold and 3-fold in XG and CG samples respectively, whereas the expression of yieF was up-regulated 66-fold and 7-fold in the same samples after 30 minutes treatment with Cr (VI). The copy numbers of chrA and yieF didn’t change after 35 days incubation with Cr (VI). The microbial communities in the Cr contaminated sampling sites were different from those in the uncontaminated samples. Especially, the relative abundances of Firmicutes and Bacteroidetes were higher while Actinobacteria was lower in the contaminated group than uncontaminated group. Further, potential indicator species, related to Cr such as Cr-remediation genera (Geobacter, PSB-M-3, Flavobacterium, and Methanosarcina); the Cr-sensitive genera (Skermanella, Iamia, Arthrobacter, and Candidatus Nitrososphaera) were also identified. These data revealed that Cr shifted microbial composition and function. Further, Cr (VI) reducing ability could be related with the expression of Cr remediation genes.